PHYSICAL AND CHEMICAL EXAMINATION OF THE DRINKING WATER IN THE PAKHAR CHOURAKI AREA OF THE MANDAWAR TEHSIL IN DAUSA DISTRICT, RAJASTHAN - Nikita Sharma; Dr Jasvinder Kaur (The Bioscan, 2024)
Growing urbanization has led to a rise in agricultural and other human activities, which have contaminated ground and surface water19. There is now insufficient demand for safe, clean drinking water, and the water that is available is now contaminated due to many factors. To improve the quality of drinking water, a variety of techniques and treatments are used. Water ought to be pure and uncontaminated by any kind of pollutants. All of its parameters, such as pH, conductivity, calcium, magnesium, total hardness, carbonate, bicarbonate, chloride, total dissolved solids, alkalinity, sodium potassium, and nitrate, should be within an allowed limit. These include organic and inorganic contaminants, heavy metals, pesticides, and more. Various samples were gathered from various sources for this purpose. Category 1: hand pump-operated boreholes with an average depth of thirty meters; Category 2: hand-dug, open wells without sealed walls with an average depth of sixteen meters. The physical-chemical and microbiological qualities of these samples (pH, conductivity, turbidity, hardness, and total dissolved solids) were examined in order to determine the level of contamination and offer suitable remedies. The human body develops a variety of ailments that are linked to contaminated water. Chemical testing can be used to identify it and then provide treatment strategies to make the water safe to drink. Every metric is validated through comparison with World Health Organization (WHO) guidelines. According to the results, categories 1 and 2 drinking waters do not have adequate quality, although they are also not within an acceptable range. A clean and safe supply of drinking water20 is a basic human necessity. All pathogens and chemicals must be removed from water (Riaz and Zia, 2020) 3. The WHO21 estimates that 75% of infections in developing nations are mostly caused by contaminated drinking water. Therefore, it is necessary to address the water's bacteriological, chemical, and physical properties (Padda and Asim, 2019) 4. The water quality index is influenced by several factors, including pH, turbidity, dissolved oxygen, and electrical conductivity. The WHO defines an acceptable pH range as 6.5–8.5. For people to maintain normal bodily processes, pH levels must be within a certain range. Enzyme activity and electrical conductivity are regulated by it in the body (Behailu et al., 2018) 5. According to (Nejat et al. 2018) 6, the optimal pH for drinking water is neutral; however, if the water becomes basic or acidic, its quality deteriorates. The water quality index is impacted by turbidity, which is the amount of suspended solid particles, both organic and inorganic (Khalid et al., 2018). Industrial pollution and salt contamination produce total dissolved solids (TDS), which indicate whether a substance is safe to use or not. Increased turbidity will result in poor water quality, possibly unfit for human consumption (Nejat et al., 2018) 6. If water hardness exceeds 200 mg/liter, it can lead to scale buildup in the distribution system and exceed 500 mg/liter, which is hazardous to human health (Lafta, 2017; Walia et al., 2017) 8,9. In order for the body to produce energy, oxygen is essential for controlling all metabolic processes.